The role of the computer in cardiac pacemaker technology. - Benedek ZM; Furman S (Pacing & Clinical Electrophysiology, 1984)
To satisfy the need for even higher performance and smaller size, pacemaker design makes use of the latest available technology. This high level of technology in pacemakers requires an even higher level of technology in the follow-up system. Present methods consisting of independent programmers far each pacer model are confusing to the operator and inadequate. The solution to pacer fallow-up developed at Montefiore consists of a three step program: 1) computer-assisted program which guides the personnel interactively through the fallow-up; 2) computer-controlled program which enables the person to send identical commands to various programmers and let the computer program identify the various pacer models; and 3) built-in program where the testing and the follow-up are performed internally to the pacer through stored programs. The system is developed in the MIIS version of the MUMPS language but was extensively modified to make conversion to other languages easy.